2020
DOI: 10.4178/epih.e2020003
|View full text |Cite
|
Sign up to set email alerts
|

Recovery time from severe acute malnutrition and associated factors among under-5 children in Yekatit 12 Hospital, Addis Ababa, Ethiopia: a retrospective cohort study

Abstract: OBJECTIVES: Recovery time from severe acute malnutrition (SAM) is often a neglected topic despite its clinical impact. Although a few studies have examined nutritional recovery time, the length of hospitalization in those studies varied greatly. Therefore, the aim of this study was to determine the recovery time from SAM and to identify predictors of length of hospitalization among under-5 children.METHODS: A retrospective cohort study was conducted among 423 under-5 children with SAM who had been admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…[ 34 ] In a study done in Ethiopia, fully vaccinated children had a higher cause of getting recovered from SAM compared to partially or not vaccinated children. [ 35 ] The current study showed an increase in SAM among those who were partially immunized. This, however, was not statistically significant after adjusting for confounders.…”
Section: Discussionmentioning
confidence: 51%
“…[ 34 ] In a study done in Ethiopia, fully vaccinated children had a higher cause of getting recovered from SAM compared to partially or not vaccinated children. [ 35 ] The current study showed an increase in SAM among those who were partially immunized. This, however, was not statistically significant after adjusting for confounders.…”
Section: Discussionmentioning
confidence: 51%
“…Adimasu et al studied effect of stunting on hospitalised children with SAM and found that many factors like associated pneumonia, stunting immunisation increased the recovery time and stay in the hospital. 15 There are no reports on the recovery time of stunted and wasted children without complications and managed in the community. This is the first report that suggests that the management of children with multiple anthropometric deficits can give rewarding results.…”
Section: Discussionmentioning
confidence: 99%
“…By understanding this problem, the FMOH of Ethiopia established the National Nutrition Program (NNP) to improve the nutrition service delivery in health facilities [ 17 ]. Most of the studies were retrospective and also lack the most important variables such as the wealth and food security status of the families and institutional factors which could affect the recovery time of children with SAM [ 18 , 19 ]. Therefore, this study tried to assess time to recovery and its predictors among children 6–59 months admitted with SAM prospectively.…”
Section: Introductionmentioning
confidence: 99%